Unilateral anterior choroidal artery infarction presenting with a temporary stupor - Dandan Yu; Xian Zhang; Wei Tang (Journal of International Medical Research)
A 73-year-old woman presented with a temporary stupor and right hemiplegia. Brain magnetic resonance imaging revealed acute infarction of the anterior choroidal artery. The clinical features associated with acute anterior choroidal artery infarction typically include hemiparesis, hemihypesthesia, and hemianopsia. However, our patient presented with a temporary stupor, which is a rare manifestation of anterior choroidal artery infarction.